2022
DOI: 10.1021/acs.inorgchem.2c02434
|View full text |Cite
|
Sign up to set email alerts
|

Periodic Trends within Actinyl(VI) Nitrates and Their Structures, Vibrational Spectra, and Electronic Properties

Abstract: Pu, and AnO 2 (NO 3 ) 2 (H 2 O) 2 •H 2 O, and the uranyl tetranitrates M 2 UO 2 (NO 3 ) 4 have been synthesized from aqueous solution and their structures determined using single-crystal X-ray diffraction. Together, these complexes represent an isostructural series of actinide complexes among the salts crystallized with the same charge-compensating cation and have been studied using vibrational spectroscopy including Raman and Fouriertransform infrared. Periodic trends in both the structural properties of thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 94 publications
2
10
0
Order By: Relevance
“…The Raman spectrum of Li 2 NpO 4 is very similar to that of Li 2 UO 4 but slightly red-shifted, as is commonly observed when moving across the actinide series. 7,46 Initial analysis suggested that the Raman spectrum of Li 2 NpO 4 is dominated by the symmetric stretching of the neptunyl cation at 693 cm −1 , displaying a typical ∼20 cm −1 red-shift compared to the uranium counterpart Li 2 UO 4 at 711 cm −1 . The Raman band associated with the symmetric -yl vibration is accompanied by a second band at 672 cm −1 in the case of Li 2 NpO 4 and 676 cm −1 in the case of Li 2 UO 4 .…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The Raman spectrum of Li 2 NpO 4 is very similar to that of Li 2 UO 4 but slightly red-shifted, as is commonly observed when moving across the actinide series. 7,46 Initial analysis suggested that the Raman spectrum of Li 2 NpO 4 is dominated by the symmetric stretching of the neptunyl cation at 693 cm −1 , displaying a typical ∼20 cm −1 red-shift compared to the uranium counterpart Li 2 UO 4 at 711 cm −1 . The Raman band associated with the symmetric -yl vibration is accompanied by a second band at 672 cm −1 in the case of Li 2 NpO 4 and 676 cm −1 in the case of Li 2 UO 4 .…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…S39 and S40†). This break in observed bonding distances with predicted ionic radii/electrostatic interactions for the actinides is known, especially in respect to enhanced covalency in An 3+ vs. Ln 3+ systems, but we are not aware of documented instances of increasing metal–ligand bond length from U 3+ to Np 3+ to Pu 3+ , 18,71–77 and such trends have not been examined for neutral arene interactions across those metals. The trend we observe here could be a result of covalency or steric effects, or both.…”
Section: Resultsmentioning
confidence: 92%
“…This ∆ν value is diagnostic for U, Np, and Pu in the +VI oxidation state and the values obtained here are consistent with other An(VI) compounds for which both Raman and IR data is available. 34 In the case of U, the calculated ∆(ν 3ν 1 ) for the crystallographically observed exo conformer is a bit underestimated in the calculation (56 cm −1 ). The gap is higher, however, for the endo conformer (74 cm −1 ), which agrees well with the difference observed in the experimental data (83 cm −1 ) and suggests the existence of both isomers under experimental conditions.…”
Section: Computational Studiesmentioning
confidence: 79%
“…Progressing from U to Np to Pu, a redshift of 43 cm −1 is observed, although the An≡O bond contracts across this series; this is similar to trends previously observed in other isostructural series of actinyl complexes and is likely derived from a decrease in overlap between the oxygen and actinide 5f orbitals as the actinides contract from U to Pu. [34][35][36][37] Two features associated with symmetric stretching of the O-C-O moiety of the acetates can be observed at ca. 890 and 955 cm −1 , corresponding to the co-crystallized acetic acid found in the lattice and bound acetate, respectively (see SI, Table ST1 for a full assignment of the spectral features).…”
Section: Vibrational and Optical Spectroscopymentioning
confidence: 99%